2017
DOI: 10.1177/1475921717725028
|View full text |Cite
|
Sign up to set email alerts
|

A novel electromechanical impedance–based model for strength development monitoring of cementitious materials

Abstract: Strength monitoring of early age concrete improves the efficiency of construction as it provides information on the optimum time for shoring removal and pre-stress transferring. Electromechanical impedance technique has been proven to be a useful tool for strength monitoring of cementitious materials. One of the key limitations of this technique is the lack of physical models, which resulted in strong reliance on statistical analysis tools to quantify the strength of structure being monitored. In this proof-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…However, the direct attachment method of the PZT often influences the appearance of the monitored structure and causes difficulties in reconfiguration of the sensor in necessary cases [18,19]. An additional important issue is the repeatability of impedance signatures, which is dependent on the structural condition of the bonding layer and the surficial condition of the target surface [20]. To overcome these issues, Annamdas et al [18] developed an indirect attachment technique using a portable structure embedded with PZTs to indirectly acquire impedance signatures from a host structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct attachment method of the PZT often influences the appearance of the monitored structure and causes difficulties in reconfiguration of the sensor in necessary cases [18,19]. An additional important issue is the repeatability of impedance signatures, which is dependent on the structural condition of the bonding layer and the surficial condition of the target surface [20]. To overcome these issues, Annamdas et al [18] developed an indirect attachment technique using a portable structure embedded with PZTs to indirectly acquire impedance signatures from a host structure.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the post statistic treatment of real admittance could better reflect the compression gain of concrete than the imaginary admittance. Lu et al (2012) proposed a PZT based sensor called ''Smart Probe'' to improve the efficiency of monitoring the concrete properties. The Smart Probe was made by using the aluminum beam with the PZT bonded on the surface and partially embedded into concrete for measurement.…”
Section: Piezoelectric Emi Methodsmentioning
confidence: 99%
“…The other statistical models, including correlation coefficient deviation (CCD) Wang et al, 2014) and mean absolute percentage deviation (MAPD) (Lu et al, 2012;Narayanan et al, 2017;Wang & Zhu, 2011) are also proposed as a valid index on strength gain monitoring of concrete. In this research, MAPD and CCD indexes are also used.…”
Section: Experiment-mortar With Different Water-to-mentioning
confidence: 99%
“…Other studies related to concrete have also been active during the past several years as many authors applied the EMI technique for predicting concrete strength. Lu et al [ 67 ] proposed an idea of using ‘Smart Probe’ to monitor the strength development of cementitious materials. Dynamic modulus of elasticity of cementitious materials was predicted with the proposed analytical model where it showed good correlation with the compressive strength of the mortar.…”
Section: Investigations On the Emi Techniquementioning
confidence: 99%